Synergies and Trade-Offs for Sustainable Food Production in Sweden: An Integrated Approach - Malin Tälle (Sustainability, 2019)
The production of food can have large impacts on sustainable development in relation to various socio-ecological dimensions, like climate change, the environment, animal welfare, livestock epidemiology, and the economy. To achieve a sustainable food production system in Sweden, an integrated approach that considers all five of these dimensions, and all parts of the food production chain, is necessary. This paper systematically reviewed the literature related to food production in Sweden, especially in association with resource distribution and recycling logistics, and identified potential sustainability interventions and assessed their effects according to the five dimensions. Participation of stakeholders across the food production chain contributed with the focus of the literature search and subsequent synthesis. In general, there were synergies between the sustainability interventions and their effect on climate change and the environment, while there often were trade-offs between effects on the economy and the other dimensions. Few interventions considered effects on animal welfare or livestock epidemiology and few studies dealt with resource distribution and recycling logistics. This indicates that there is a need for future research that considers this in particular, as well as research that considers the whole food production chain and all dimensions at once, and investigates effects across multiple scales.